Innovative base-isolated building with large mass-ratio TMD at basement for greater earthquake resilience (Future Cities and Environment, 2015)
Tuned mass dampers (TMD) have been used for the reduction of building responses to wind loading in many high-rise buildings. An innovative and resilient base-isolated building with a large mass-ratio TMD is introduced here primarily for earthquake loading in which the large mass-ratio TMD is located at basement. This new hybrid system of base-isolation and structural control possesses advantageous features compared to existing comparable systems with a TMD at the base-isolation story. The TMD stroke can be reduced to a small level with the use of an inertial mass damper and its reaction can be limited to a lower level by detaching its connection to ground. The proposed hybrid system has another advantage that the TMD mass does not bring large gravitational effect on the building itself. It is demonstrated that the proposed hybrid system is robust both for pulse-type ground motions and long-period, long-duration ground motions which are regarded as representative influential ground motions.